Pemanfaatan Sumber Daya dan Teknologi pada Pengajaran Bahasa Indonesia - Pani Pani; Niken Aprilla; Natasya Lady Munaroh (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research aims to utilize the resources and technology used by teachers in Indonesian language education using qualitative descriptive methods. Data was collected through interviews and observations of 5 Indonesian language teachers. The research instrument is a semi-structured interview guide which was prepared based on a literature review and research objectives. Interviews were conducted either face-to-face or via communication tools such as telephone or video call and lasted 45-60 minutes per session. All interviews were recorded with the consent of the participants. Data analysis was carried out descriptively to identify main themes regarding the impact of the use of technology on Indonesian language learning, challenges for the future, and strategies for optimizing the use of technology. The validity and reliability of the interview is guaranteed through thorough preparation, consistent execution, and thorough analysis. It is hoped that the results of this research can provide significant recommendations for further development of the use of technology in Indonesian language education.